Squamous Cell Carcinoma With Hyper-IgE Syndrome: A Case Report. Issue 6 (August 2018) - Sasihuseyinoglu, Ayse S.; Yilmaz, Mustafa; Altintaş, Derya U.; Dogruel, Dilek; Serbes, Mahir; Uğuz, Aysun H.; Kiroğlu, Mete
Abstract : Background: Hyper-immunoglobulin E syndrome (HIES) is a rare primary immunodeficiency disease characterized by recurrent infections and elevated levels of serum immunoglobulin E, usually over 2000 IU/mL. Recurrent and chronic infection of the epidermis and squamous epithelium may also be a cause of squamous cell carcinoma (SCC). SCC is rare with HIES. Case Report: A 17-year-old male patient who was diagnosed as HIES was admitted with purulent right ear discharge. The patient had a history of eczema starting from the age of 7 months and a history of recurrent middle ear infection starting from the age of 5. Biopsy specimens were taken from the lesion in the external auditory canal, and the lesion was reported as SCC. Conslusion: Patients with autosomal recessive HIES are at an increased risk for infections and malignancies. SCC should be considered in the differential diagnosis of the patients presenting with recurrent middle ear infections and immunodeficiency.